HYPERTENSIVE CRISIS: CLINIC, EMERGENCY CARE - G.T. Mamedova (Western European Studies, 2024)
A Hypertensive Crisis Is “An Acute, Pronounced Increase In Blood Pressure, Accompanied By Clinical Symptoms And Requiring An Immediate, Controlled Reduction In Order To Prevent Or Limit Target Organ Damage” [1]. The Key Point In This Definition Is Not The Level Of Blood Pressure (BP), But The Severity Of Clinical Symptoms; This Is What Is Most Important For Diagnosing The Type Of Hypertensive Crisis And Choosing Further Tactics For Patient Management. However, The Accuracy Of Blood Pressure Measurements Is Also Important
Keywords: Dissecting Aortic Aneurysm; Pulmonary Edema; Myocardial Infarction